GE_GERICHTE C/19811/2016 vom 30. Oktober 2018 - GE Cour de justice (2018)
FAIT DE DOUBLE PERTINENCE ; COMPÉTENCE | CO.319.al1; CPC.59.al1.letb; CPC.60; CO.320.al1; CO.320.al2; LTPH.1.al1.leta; CPC.4; Cst.122.al2